Warranty period of normal CCTA and [15O]H2O PET in chest pain patients. (3rd October 2022) - Jukema, R; Maaniitty, T; Van Diemen, P; Berkhof, H; Raijmakers, P; Sprengers, R; Planken, R; Knaapen, P; Saraste, A; Danad, I; Knuuti, J
Abstract: Background: Normal coronary computed tomography angiography (CTA) and positron emission tomography (PET) are associated with an excellent prognosis. Hitherto, data on the warranty period of normal coronary CTA and normal myocardial blood flow (MBF) by PET are scarce. Purpose: To determine the event-free period after normal coronary CTA and PET results. In addition, to determine whether PET MBF imaging confers additional prognostic value beyond coronary anatomy in symptomatic patients. Methods: Patients with suspected but not previously diagnosed coronary artery disease (CAD) who underwent coronary CTA or [ 15 O]H2 O PET were categorized based upon coronary CTA as no CAD, non-obstructive CAD or obstructive CAD. A hyperemic MBF <2.3 ml/min/g was considered abnormal and indicative for ischemia. A cumulative risk below 5% against death and myocardial infarction (MI) was used to define the warranty period. Results: Of 2575 included patients (mean age 61.4±9.9 years, 41% male) 1319 (51.2%) underwent coronary CTA only, 1237 (48.0%) underwent both coronary CTA and PET and 19 (0.74%) patients underwent PET imaging only. During a median follow-up of 7.0 years 163 deaths and 68 MIs occurred. The warranty period for patients without any CAD was >10 years. Patients with non-obstructive CAD had a 5 year warranty period. In patients with no, non-obstructive or obstructive CAD on CTA, normal PET extended the warranty period with ≥2 years. The warranty period of patients with non-obstructive CAD or normal perfusion varied between 2.5 and >10 years for patients with or without clinical risk factors. Conclusions: As standalone imaging, the warranty period for a normal coronary CTA is >10 years, whereas patients with non-obstructive CAD have a warranty period of 5 years. Independent of coronary anatomy normal perfusion imaging has additional prognostic value and extends the warranty period by ≥2 years. Funding Acknowledgement: Type of funding sources: None.